1991
DOI: 10.1002/abio.370110419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous cycllc amp on catabolite repression of cellulase formation in aspergillus nidulans

Abstract: The addition of 1 ruM cyclic AMP to induced and repressed cultures of Aspergillus nidula7~s and its mutant strain (CRR 141) resistant to catabolite repression was fully capable of releasing the wild type from catabolite repression while it caused hyperproduction of cellulases in glycerol repressed cultures. The relief of the catabolite repression was also accompanied by a dramatic drop in enhanced protease levels, thereby indicating that the synthesis of proteases (during the cataholite repression) is under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The combined extracts lost no activity suggesting incapability of proteases to inactivate both glucanases. , WOOD et al 1984SIDHU and SANDHU 1985, KALRA et al 1986, BAGGA et al 1989. Thus, in common with other cellulolytic microorganisms, S. albaduuncus utilizes cellulose for growth and regulates cellulase biosynthesis by feedback control in the presence of glycerol by underlying the phenomenon of catabolite rcprcssion.…”
Section: Resultsmentioning
confidence: 91%
“…The combined extracts lost no activity suggesting incapability of proteases to inactivate both glucanases. , WOOD et al 1984SIDHU and SANDHU 1985, KALRA et al 1986, BAGGA et al 1989. Thus, in common with other cellulolytic microorganisms, S. albaduuncus utilizes cellulose for growth and regulates cellulase biosynthesis by feedback control in the presence of glycerol by underlying the phenomenon of catabolite rcprcssion.…”
Section: Resultsmentioning
confidence: 91%
“…This study substantiates the work of Nochure et al (1993) who demonstrated fructose as the best inducer of Avicellase in Clostridium thermocellum. Bagga et al (1989) identified lactose as the best inducer of endoglucanase and cellobiohydolase. Trehalose has been demonstrated as the best inducer of cellulases in a Clostridium sp.…”
Section: Evaluation Of Carbon Sources For Induction/repression Of Glumentioning
confidence: 98%
“…Also, catabolite repression of cellulase formation in fungi has been reported frequently. For instance, Bagga, Sandhu & Sharma (1989) demonstrated that the addition of glucose to a medium containing CMC Significantly repressed all com ponents of the cellulase complex of AspergillUS' nidulans. Horton & Keen (1966) showed that 500 I-lM glucose was sufficient to repress the cellulase of the plant pathogen Pyrenochaeta terrestris.…”
Section: Discussionmentioning
confidence: 99%